Design and Development of Residential Estimated Bill Electricity Calculator Using Android Studio - Mohd Jaswadi, Nurul Ismahani; Jamail, Norakmal; Kamarudin, Qamarul Ezani (Evolution in Electrical and Electronic Engineering, 2023)
The Residential Estimated Bill Calculator Application is a simple and straightforward mobile application created using Android Studio. By offering a trustworthy and open platform for bill estimation, it seeks to allay residents’ rising worries about their electricity bills. The goal of this project is to design a residential bill estimated calculator and to analyze the performance of the calculation application for residency. The other purpose of this application development is to compare the result of the application with the Tenaga Nasional Berhad (TNB) bill system. The system was designed using Android Studio and Flutter. The coding was run in the Android Studio using the Dart Language. Flutter was used to build cross-platform mobile applications. The performance of the application was analyzed by using the system. Once the system shows the desired result interface, it means the system functionally works smoothly. The TNB’s bill calculator system was used as a reference to compare the results of the residential estimated bill calculator whether it was accurate and trustworthy. About 90% of the system that was developed was accurate with the TNB’s system. The residential estimated bill calculator was successfully designed, and the performance of the calculation application was analyzed with the use of Flutter. Based on the comparison result, the residential estimated bill calculator is more convenient because the system requires the user’s house load but the result is less than 10% more accurate. In conclusion, the developed system was a user-friendly type and it also went through the analysis step to make sure that the calculation results were accurate with the TNB’s system.